2012
DOI: 10.1159/000339056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of IL-1ß on Galactose Intestinal Absorption in Rabbits

Abstract: Background/Aims: Recent studies from our laboratory have shown that nitric oxide is involved in the IL-1β-induced inhibition of D-fructose intestinal transport in rabbits. The aim of this work was to further the studies of IL-1β effect on D-galactose absorption in a septic state induced by intravenous administration of this cytokine. Methods: Galactose intestinal absorption was assessed employing three techniques: sugar uptake in jejunum everted rings, transepithelial flux in Ussing-type chambers and uptake as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In addition, MG 132 has not effect “per se” in fructose absorption (data not shown). The results agree with previous studies carried out in our laboratory in relation to galactose intestinal absorption (Viñuales et al, ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, MG 132 has not effect “per se” in fructose absorption (data not shown). The results agree with previous studies carried out in our laboratory in relation to galactose intestinal absorption (Viñuales et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The possible involvement of the proteasome was also evaluated, on intestinal tissue and BBMV, using the potent cell‐permeable proteasome inhibitor MG 132 administered iv at 250 μg/kg bw 15 min before IL‐1β treatment (García‐Herrera et al, ; Viñuales et al, ). The results showed that MG 132 completely suppressed the inhibitory effect of Il‐1β on D ‐fructose intestinal transport (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…158 Among the carriers upregulated by NF-κB is the Na + /H + exchanger NHE3, 159 carriers downregulated by NF-κB include SGLT1. 160 NF-κB presumably regulates the expression of multiple further transport proteins and/or several signaling cascades involved in transport regulation. For instance, NF-κB downregulates the expression of the serum and glucocorticoid inducible kinase SGK1, 158 a powerful regulator of a wide variety of channels, carriers and Na + /K + ATPase.…”
Section: Mechanisms Employed In Ampk-mentioning
confidence: 99%